Um novo critério para seleção de variáveis usando o Algoritmo das Projeções Sucessivas - Soares, Sófacles Figueiredo Carreiro (2010)
This study proposes a modification in the Successive Projections Algorithm (SPA), that makes models of Multiple Linear Regression (MLR) more robust in terms of interference. In SPA, subsets of variables are compared based on their root mean square errors for the validation set. By taking into account the statistical prediction error obtained for the calibration set, and dividing by the statistical prediction error obtained for the prediction set, SPA can be improved. Also taken into account is the leverage associated with each sample. Three case studies involving; simulated analytic determinations, food colorants (UV-VIS spectrometry), and ethanol in gasoline (NIR spectrometry) are discussed. The results were evaluated using the root mean square error for an independent prediction set (Root Mean Square Error of Prediction - RMSEP), graphs of the variables, and the statistical tests t and F. The MLR models obtained by the selection using the new function were called SPE-SPA-MLR. When an interferent was present in the prediction spectra, almost all of the models performed better than both SPA-MLR and PLS. The models when compared to SPA-MLR showed that the change promoted better models in all cases giving smaller RMSEPs and variable numbers. The SPE-SPA-MLR was not better in some cases, than PLS models. The variables selected by SPA-SPE-MLR when observed in the spectra were detected in regions where interference was the at its smallest, revealing great potential. The modifications presented here make a useful tool for the basic formulation of the SPA.